An assessment of the utility of LiDAR data in extracting base-year floorspace and a comparison with the census-based approach. (July 2015) - Shiravi, Sajad; Zhong, Ming; Beykaei, Seyed Ahad; Hunt, John Douglas; Abraham, John E
A literature review indicates that most integrated land-use transport models (ILUTMs) estimate base-year floorspace data according to limited population and employment data provided by the census and, in general, the accuracy is unknown. This paper assesses the utility of airborne Light Detection And Ranging (LiDAR) technology as a valuable tool for extracting base-year floorspace using the following three datasets: a geographic vector building footprint layer, a LiDAR dataset, and field survey data for the south side of the City of Fredericton, Canada. It is found through a statistical comparison with the results from the field survey that LiDAR data can be used to extract buildings and estimate floorspace with a good degree of accuracy. Further, two base-year floorspace estimation methods, one based on the LiDAR data and the other on census data, are compared. In general, our results show that the traditional census-based approach may not be reliable for estimating base-year floorspace. Using the extracted floorspace from the LiDAR data as the basis, for residential floorspace estimation the average absolute percentage errors (APE) of the census-based approach is 16% and the 95th percentile APE is 34%. On the other hand, for employment floorspace estimation, the accuracy of the census-based approach is even lower, with average errors of 50% or higher and the 95th percentile APEs as high as 163% up to 400% for several land-use categories. All the above statistics indicate that the traditional census-based approach is unreliable and inaccurate for modelers and planners to prepare their base-year floorspace, and therefore suggest a better way be explored. Study results clearly show the utility of LiDAR data and imply that it can be used as a powerful add-on for ILUTMs in general.